VULNERABILITY ASSESSMENT UNTUK ANALISIS TINGKAT KEAMANAN PADA SISTEM INFORMASI REPOSITORI KARYA ILMIAH POLITEKNIK XYZ - Riyan Farismana; Dian Pramadhana (Lembaga Pengembangan Kinerja Dosen, 2023)
The large role of information systems in supporting the success of organizational business processes, making security issues an absolute thing to maintain. The world of education also makes information systems a place to store and manage academic data, one of which is scientific work. Polytechnic XYZ has a repository information system for scientific papers and student final assignments managed by librarians to facilitate the archiving of scientific papers by students. Vulnerability assessment is carried out through the stages of information gathering, vulnerability scanning, vulnerability analysis using tools such as robtex.com and Owasp ZAP to find out the security gaps that exist in the repository information system, so that the intellectual property contained therein can be maintained. from the test results found 22 vulnerabilities from high to informational levels, and in the final stage a generating report is carried out which contains a description of the vulnerabilities and solutions to fix dangerous vulnerabilities.